Kahang-bakal a Disaster Risk Reduction and Management Operation and Research Complex - Lapatha, Micah S.; Ong, Simoun (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
Natural disasters have been a norm for our country. This is to be expected as the Philippines is located both in the Pacific Ring of Fire and the Typhoon belt. For the past 3 years, the country was ranked as the third in the World Risk Index, a study released by the United Nations University's Institute of Environment and Human Resources. As the study takes into consideration the geographical and geophysical attributes of a country which is under the sphere of natural hazards, it also evaluates a country's vulnerability with regards to the sphere of society. The first one deals with the exposure of the country to natural hazards like sea level rise, flooding, earthquakes, and storms. The latter deals with the affected population. It is the sum of their coping ability, susceptibility, and adaptation. The first one is beyond our control, there are only limited actions that we can do to changes our exposure to natural hazards. Despite that, the second sphere that disaster risk reduction and management initiatives/programs should significantly involve is exceptionally open to knowledge and innovation which is the sphere of society.
include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Disaster Risk Reduction and Management -- Philippines